Analyzing movement behavior of zebrafish in different sized confined areas - Quach Kha Quang,; Nguyen Quoc Anh, (Vietnam Journal of Science and Technology, 2022)
Movement behavior of zebrafish (Danio rerio) was analysed according to different sizes of observation arena (four sizes:and ). The observation arena was separated into corner, boundary and central areas based on experimental data. The results showed that the shapes of the corner, boundary and central areas were accordingly different in different sizes of the arena. Individuals stayed in the boundary zone for a substantial proportion (approximately 55-58 %) of the observation period while in the corner zone they stayed for the shortest time period (approximately 12-14 %). Movement parameters (speed, acceleration, etc.) of each individual varied in different areas on different sizes and speed was highest in the size of while acceleration was highest in the size of . These reveal that the movement behaviors of zebrafish were affected by different sizes of arenas, at larger sizes they move more actively compared to smaller sizes. However, Transition probability matrices (TPMs) of moving between different areas in the observation were stable. These findings imply that there is a stereotypic inner state that maintains basic behaviors in animals. Information from this work would provide backgrounds of real-life process mechanism and would be useful for monitoring in response to environmental changes in practical aspect and be applicable to a wide range of fields including pharmacology, neurology, and genetics.